2023
DOI: 10.3390/genes14030699
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects of GA-Responsive Dwarfing Gene Rht13 on Plant Height, Peduncle Length, Internodal Length and Grain Yield of Wheat under Drought Stress

Abstract: Reduction in plant height is generally associated with an increase in lodging resistance, drought tolerance and grain yield of wheat worldwide. Historically, a significant increase in grain yield was observed through the introduction of semi-dwarf wheat varieties utilizing the gibberellic acid-insensitive Rht genes (Rht1 or Rht2). The gibberellic acid sensitive (GA-sensitive) reduced height (Rht) genes are available that are alternatives to gibberellic acid insensitive (GA-insensitive) Rht genes, having a neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, complete understanding of different morpho-physiological characters, such as plant height, is important in obtaining high grain yield. Khalid et al [28] reported that reduction in plant height is generally associated with an increase in lodging resistance, drought tolerance and grain yield. It was observed that the character of the straw pith in cross section in the present investigation in most of the varieties expressed thin to medium size.…”
Section: Flag Leaf and The Whole Plants Characteristicsmentioning
confidence: 99%
“…However, complete understanding of different morpho-physiological characters, such as plant height, is important in obtaining high grain yield. Khalid et al [28] reported that reduction in plant height is generally associated with an increase in lodging resistance, drought tolerance and grain yield. It was observed that the character of the straw pith in cross section in the present investigation in most of the varieties expressed thin to medium size.…”
Section: Flag Leaf and The Whole Plants Characteristicsmentioning
confidence: 99%
“…Current semi-dwarf wheats owe their lower height to the reducing genes Rht1, Rht2 and Rht3 that are insensitive to gibberellic acid (Khalid et al, 2023). These genes reduce plant height but also decrease leaf and stem cell size, coleoptile length, and seedling leaf area (Hoogendoorn et al, 1990).…”
Section: Introductionmentioning
confidence: 99%